Effect of Catecholamines on the Adenosine 3′:5′-Cyclic Monophosphate Concentrations of Clonal Satellite Cells of Neurons - Gilman, Alfred G. (1971)
The effects of potential neurohormones on the intracellular concentrations of adenosine 3′:5′-cyclic monophosphate have been examined with three clonal lines of cultured glial tumors. In all cases, norepinephrine and isoproterenol produced striking elevations of the intracellular concentrations of the cyclic nucleotide. The response was mediated by a β-adrenergic receptor. This effect is hypothesized to represent a molecular mechanism for neuronal-glial communication coupled to concurrent communication between neurons.